Bimetallic core–shell nanoparticle arrays at liquid–liquid interface for the degradation and monitoring of dye pollutants in situ by surface-enhanced Raman spectroscopy. Issue 10 (27th February 2023) - Wei, Yujiao; Guo, Jinhu; Wang, Liming; Qu, Cheng; Geng, Yuchuang; He, Shengnan; Su, Mengke; Liu, Honglin
Abstract : Bimetallic core–shell nanoparticle arrays at liquid–liquid interface for the degradation and monitoring of dye pollutants in situ by SERS. Abstract : In situ monitoring of chemical reactions has attracted great attention in many fields. Herein, we successfully in situ track the degradation reaction process of a dye pollutant, methylene blue (MB), on the liquid–liquid interface (LLI) of bimetallic gold core–silver shell nanoparticles (Au@AgNPs) by surface-enhanced Raman spectroscopy (SERS). The optimized LLI bimetallic array of Au50 @Ag10 NPs exhibits ultrahigh SERS enhancement and excellent catalytic activity. Results evidenced a detection limit of MB down to 1 ppb, and the degradation rate of Au@AgNPs was as high as 85.2% in 30 s, relying on the excellent self-healing properties of nanoarrays. Furthermore, as a practical SERS analyzer, the LLI bimetallic array was used to detect trace amounts of other harmful dyes, including Rhodamine 6G (R6G) and crystal violet (CV) in pure or complex media. Our LLI bimetallic array exhibits a new orientation for monitoring catalytic reactions involving highly toxic, hazardous, or costly targets in food security fields in the future.